Komponen Utama Pengembangan Kurikulum dan Langkah-Langkah Pengembangannya - Ahmad Ilham Fadli; Agus Pahrudin; Agus Jatmiko; Koderi Koderi (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The curriculum is an idea in the implementation of education, without the formation of the curriculum, the results of learning are not directed and have no definite goals. The purpose of this research is to find out the main components of curriculum formation before the curriculum is developed into a better curriculum. The research method used in this research is library research. Data collection techniques by exploring data through literature review, reading, reviewing, and recording data from various sources of relevant articles, journals and books. The results of this research on curriculum development elements are expected to help in solving educational problems in developing the curriculum at this time.